1989
DOI: 10.1164/ajrccm/139.1.194
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cigarette Smoking with Decreased Numbers of Circulating Natural Killer Cells

Abstract: To investigate the relationship between cigarette smoking and the level of circulating natural killer (NK) cells, we studied 282 subjects from a population-based, stratified random sample of healthy persons. NK cells were enumerated by flow cytometry using the monoclonal antibody anti-Leu 11A. Cigarette smokers had a significantly lower proportion of NK cells than did subjects who had never smoked (5.5 +/- 0.3% versus 7.4 +/- 0.4% of lymphoid cells; p = 0.0002). NK cells were also decreased among ex-smokers (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
3
3

Year Published

1992
1992
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(87 citation statements)
references
References 10 publications
4
77
3
3
Order By: Relevance
“…Furthermore, we have found a greater increase in NKCA in ex-smokers after health education than that in current smokers, although age distribution in the two groups was different. Tollerud and his associates 32) report that NK cells were also decreased among ex-smokers, including subjects who had not smoked for more than 20 yr. Many researches have demonstrated that smoking behavior contradicted with exercise habits [33][34][35] .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we have found a greater increase in NKCA in ex-smokers after health education than that in current smokers, although age distribution in the two groups was different. Tollerud and his associates 32) report that NK cells were also decreased among ex-smokers, including subjects who had not smoked for more than 20 yr. Many researches have demonstrated that smoking behavior contradicted with exercise habits [33][34][35] .…”
Section: Discussionmentioning
confidence: 97%
“…Animal experiments have shown that lower NK cell activity is associated with higher cancer incidence, while studies on NK cell activity on humans have found significantly lower NK activity among smokers compared to non-smokers (Ferson et al 1979;Ginns et al 1985;Phillips et al 1985;Talmadge et al 1980). Another study found that smoking decreased both the quantity and function of NK cells, and the quantity and function remained impaired after smoking cessation, while other white blood cell functions returned to normal (Tollerud et al 1989). Other research has linked lower initial NK cell activity to colorectal cancer recurrence and an advanced colorectal cancer stage at diagnosis (Tartter et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…As for life style, it was reported that reduction of NK cell functions was associated with cigarette smoking [34][35][36][37][38] , shortened daily sleep 17) , disturbed sleep [39][40][41] , circadian rhythm (high activity in the morning and low activity at night) [42][43][44][45] , and excessive physical exercise 46,47) . Conversely, healthy life styles (i.e., good sleep, adequate physical exercise, and so on) were associated with increases of NK cell functions [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%